VietNam mosaic of contrasts II= Vietnam, mosaïque de contrastes - Réhahn (Hồng Đức, 2016)
Vietnam Mosaic of Contrasts is a compilation of 145 photos which depict Vietnam, the photographer's now homeland. It is a visual tribute to the people, young and old, the exquisite landscape and the diversity of cultures in Vietnam and is a culmination of the first 3 years of his life here.